Mutation in a highly conserved glycine residue in strand 5B of plasminogen activator inhibitor 1 causes polymerisation - Iwaki, Takayuki; Nagahashi, Kotomi; Takano, Katsuhiro; Suzuki-Inoue, Katsue; Kanayama, Naohiro; Umemura, Kazuo; Urano, Tetsumei (Thrombosis and Haemostasis, 2017)
Serpinopathy is characterised as abnormal accumulation of serine protease inhibitors (SERPINs) in cells and results in clinical symptoms owing to lack of SERPIN function or excessive accumulation of abnormal SERPIN. We recently identified a patient with functional deficiency of plasminogen activator inhibitor-1 (PAI-1), a member of the SERPIN superfamily. The patient exhibited life-threatening bleeding tendencies, which have also been observed in patients with a complete deficiency in PAI-1. Sequence analysis revealed a homozygous singlenucleotide substitution from guanine to cytosine at exon 9, which changed amino acid residue 397 from glycine to arginine (c.1189G>C; p.Gly397Arg). This glycine was located in strand 5B and was well conserved in other serpins. The mutant PAI-1 was polymerised in the cells, interfering with PAI-1 secretion. The corresponding mutations in SERPINC1 (anti-thrombin III) at position 456 (Gly456Arg) and SERPINI1 (neuroserpin) at position 392 (Gly392Glu) caused an anti-thrombin deficiency and severe dementia due to intracellular retention of the polymers. Glycine is the smallest amino acid, and these mutated amino acids were larger and charged. To determine which factors were important, further mutagenesis of PAI-1 was performed. Although the G397A, C, I, L, S, T, and V were secreted, the G397D, E, F, H, K, M, N, P, Q, W, and Y were not secreted. The results revealed that the size was likely triggered by the polymerisation of SEPRINs at this position. Structural analyses of this mutated PAI-1 would be useful to develop a novel PAI-1 inhibitor, which may be applicable in the context of several pathological states.
Keywords: Plasminogen activator inhibitor 1; SERPINE1; mutation; bleeding disorder; serpinopathy